Physicochemical characterization, emulsifying and antioxidant properties of the polysaccharide conjugates from Chin brick tea (Camellia sinensis). (30th November 2022) - Li, Qian; Zhao, Tiantian; Shi, Jinglan; Xia, Xinyi; Li, Jing; Liu, Lu; McClements, David Julian; Cao, Yi; Fu, Yinxin; Han, Lingyu; Lin, Hongyi; Huang, Jialu; et al.
Graphical abstract: Highlights: Tea polysaccharide conjugates (TPC) with different molecular weights were prepared. The emulsifying activity of TPC was negatively with their molecular weights. The emulsion stabilization of TPC was positively with their molecular weights. Physicochemical characteristics of TPC greatly impact their functional properties. Abstract: Tea polysaccharide conjugate fractions (TPCs) with different molecular weights (TPC-40, TPC-60, and TPC-80, MW  = 1355 to 204 kDa) were prepared from Chin brick tea using graded alcohol precipitation. The physiochemical and functional properties of TPCs were investigated. Results showed that TPC-80 (204 kDa) had the highest antioxidant activity attributed to its higher phenolic and theabrownin contents. Moreover, this fraction had the highest surface pressure (16.2 ± 0.9 mN/m), but the lowest interfacial dilatational modulus (30.3 ± 2.2 mN/m) than TPC-40 (1355 kDa) and TPC-60 (955 kDa). As a result, TPC-80 had the highest emulsifying activity but the lowest emulsion stabilizing properties due to its fastest adsorption kinetics but the relatively thin interfacial coating on the oil droplets. Overall, our results indicate that the chemical compositions and structural characteristics of TPCs significantly impact their functional attributes. TPCs have the potential to be a novel natural antioxidant emulsifier in food industry.